Модифицированный метод целевой координации задач управления сетевыми ресурсами в территориально-распределенных телекоммуникационных системах - Лемешко, О. В.; Евсеева, О. Ю.; Симоненко, Д. В. (УНДІЗ, 2007)
The modified method of coordination in solving of the problem network resources control in the geographically distributed telecommunication system (TS) is offered. Modification consists in using of the procedure of TS functioning stability estimating. This procedure is based on the using of the Lyapunov’s stochastic functions. The implementation of the offered method allows to heighten of control decisions scalability.
Keywords: сетевые ресурсы